2018
DOI: 10.1002/ejhf.1292
|View full text |Cite
|
Sign up to set email alerts
|

Activity and outcomes of a cardio‐oncology service in the United Kingdom—a five‐year experience

Abstract: Through the establishment of a cardio-oncology service, it is feasible to achieve high rates of cardiac optimisation and cancer treatment continuation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
104
1
10

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(120 citation statements)
references
References 25 publications
5
104
1
10
Order By: Relevance
“…It is most commonly defined as meeting three out of five phenotypic criteria: low physical activity, unintentional weight loss, slow walking speed, weak grip strength, and/or exhaustion. 211 Development of cardiac dysfunction after anthracycline therapy is associated with similar outcomes as other nonischaemic cardiomyopathies. 206 Adiposity is associated with increased ventricular-arterial stiffness among the elderly and suggest a potential role in the development of HF.…”
Section: Comorbiditiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is most commonly defined as meeting three out of five phenotypic criteria: low physical activity, unintentional weight loss, slow walking speed, weak grip strength, and/or exhaustion. 211 Development of cardiac dysfunction after anthracycline therapy is associated with similar outcomes as other nonischaemic cardiomyopathies. 206 Adiposity is associated with increased ventricular-arterial stiffness among the elderly and suggest a potential role in the development of HF.…”
Section: Comorbiditiesmentioning
confidence: 99%
“…206 Adiposity is associated with increased ventricular-arterial stiffness among the elderly and suggest a potential role in the development of HF. 211 Prospective registries are established. 208 Cancer therapies are associated with side effects including up to nine categories of cardiovascular complications.…”
Section: Comorbiditiesmentioning
confidence: 99%
“…23 The third phase of prevention consists of long-term surveillance of cancer survivors. 84 Recent data from Pareek et al 84 demonstrated the effectiveness of these services. CV disease can develop many years after diagnosis and treatment of cancer.…”
Section: Diagnosis and Preventionmentioning
confidence: 99%
“…Treating heart failure and cancer, two malignant diseases, at the same time is challenging for both oncologists and cardiologists . Many centres of excellence have established cardio‐oncology services to evaluate the risk of cardiotoxicity, monitor the effects of therapy on cardiac function, ensure that curative treatment for cancer is not inappropriately withheld and manage patients who develop cardiac dysfunction and heart failure whilst being treated for cancer . We must hope that all patients with heart failure have access to similar resources for their care when needed and not just those with two malignant diseases rather than just one.…”
mentioning
confidence: 99%